Adaptation of settlement strategies to environmental conditions in southern Slovakia in the Neolithic and Eneolithic - Peter Tóth; Peter Demján; Kristina Griačová (Documenta Praehistorica, 2011)
Environmental conditions such as climate, topography, and soil conditions had an impact on prehistoric settlement strategies. By studying changes in settlement structure in the Nitra, Hron and Ipel’ valleys in southern Slovakia over the course of the Neolithic and Eneolithic, preferences for various climatic and topographic environments in different periods can be seen. Besides cultural and socio-economic factors, it can also be expected that changes in climate contributed to change in settlement patterns. Climatic changes in Neolithic and Eneolithic have been identified and correlated with major changes in socio-economic structure, as well as with known climate fluctuations in the North Atlantic area.